Multiscale, presence‐only habitat suitability models: fine‐resolution maps for eight bat species. Issue 4 (2nd July 2013) - Bellamy, Chloe; Scott, Christopher; Altringham, John
Summary: To manage anthropogenic environmental change for the benefit of biodiversity, we must improve our understanding of the complex relationships between organisms and their environment. We have developed multiscale habitat suitability models (HSMs) for bats, a mobile group of mammals, for a geographically varied region of the UK. We ask whether the models have sufficient accuracy to contribute to informed decision‐making in habitat management and in minimizing the impact of climate change and human infrastructural development. We used acoustic surveys supplemented by catching to gather presence data for eight species from 30 sites across the south of the Lake District National Park in NW England. Species were identified by manual and automated extraction and analysis of echolocation calls. Fine‐resolution (50 and 100 m) habitat maps were generated at twelve spatial scales by calculating the variables across squares of increasing size, from 100 to 6000 m, around each focal 50 or 100 m square. Presence‐only HSM software, MaxEnt, was used to determine the predictive power of each habitat variable at each scale. Multiscale models included data for each variable at the scale at which it had the strongest relationship with the presence of each species. The best multiscale models were selected using fivefold cross‐validation, with backwards, stepwise variable removal, whilst minimizing residual spatial autocorrelation and sampling bias. Further tests with independent field data indicated good model transferability across the entire National Park. Foraging bats were generally most strongly associated with variables measured at small spatial scales and distance measures. However, each species responded differently across the range of scales, and strong associations were also found at the largest scale of analysis (6000 m). Synthesis and applications . The best models for determining habitat suitability had few variables, making them easy to interpret and use in practical conservation planning. The approach is applicable to any taxa for which reliable presence records are available, providing insight into the potential impacts of land‐use and environmental change. Maps identify areas of conservation concern, such as hot spots for diversity, rare or vulnerable species and potential or threatened network corridors, making them useful for ecological impact assessment of proposed developments, and to conservation managers planning habitat creation or improvement. Abstract : The best models for determining habitat suitability had few variables, making them easy to interpret and use in practical conservation planning. The approach is applicable to any taxa for which reliable presence records are available, providing insight into the potential impacts of land‐use and environmental change. Maps identify areas of conservation concern, such as hot spots for diversity, rare or vulnerable species and potential or threatened network corridors, making them useful for ecological impact assessment of proposed developments, and to conservation managers planning habitat creation or improvement.